Application of Abstract Data Types to the Implementation of Data Base Management Systems - Baroody, Anthony; DeWitt, David (University of Wisconsin-Madison Department of Computer Sciences, 1977)
This research describes the use of abstract data types as a design and implementation tool for data base management systems. Abstract data types, represented by generic objects and generic procedures, are used to implement a network data base management system. Generic objects are used to represent the data model, instantiations of the objects to represent the user's schema and subschema, and generic procedures to implement the data manipulation language verbs. Traditional database management system design approaches are described in which run-time interpretation of the schema and subschema is employed to preserve data independence. Application of abstract data types to the design of a data base management system permits the elimination of the time-consuming run-time interpretation without suffering any loss of data independence. Data abstractions which represent the logical structure of the database are bound at compile-time to the user's program. The data manipulation language verbs included in the user's source program are implemented as parameterized calls to the procedures bound to those abstract data types which are used to represent the logical structure of the database.